Implementation of Rheumatic Exercise to Manage Chronic Pain in a Patient with Rheumatoid Arthritis: A Family Nursing Case Study - Asep Gunawan; Rizky Arif Susilo Putra (Yayasan Inspirasi El Burhani, 2026)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent joint inflammation, pain, stiffness, and decreased functional ability, significantly affecting patients' quality of life. Chronic pain is one of the primary nursing problems experienced by individuals with RA. Rheumatic exercise is a non-pharmacological intervention that can improve joint flexibility, muscle strength, and functional mobility while reducing pain intensity. Family involvement is essential in supporting the continuity of nursing interventions at home. Objective: This case study aimed to describe the implementation of rheumatic exercise in managing chronic pain in a patient with rheumatoid arthritis through family nursing care. Method: his descriptive case study applied the family nursing process, including assessment, nursing diagnosis, planning, implementation, and evaluation. The subject was a female patient diagnosed with rheumatoid arthritis who experienced chronic pain, joint stiffness, and limitations in daily activities. Rheumatic exercise was performed once daily for approximately 15 minutes over three consecutive days, accompanied by education and active family participation to encourage independent exercise practice at home. Result: The patient's pain intensity gradually decreased from a Numeric Rating Scale (NRS) score of 5 before the intervention to 4 on the first day, 2 on the second day, and 0 on the third day. Improvements were also observed in joint mobility, physical function, and the patient's confidence in performing daily activities. Family members demonstrated adequate knowledge and skills to support the continuation of rheumatic exercise at home. Conclusion: The implementation of rheumatic exercise within family nursing care effectively reduced chronic pain and improved functional mobility in a patient with rheumatoid arthritis. This intervention is simple, safe, cost-effective, and may serve as an effective complementary nursing strategy for chronic pain management in community and home care settings.